If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 3)(6 + -3x) = 0 Reorder the terms: (3 + 2x)(6 + -3x) = 0 Multiply (3 + 2x) * (6 + -3x) (3(6 + -3x) + 2x * (6 + -3x)) = 0 ((6 * 3 + -3x * 3) + 2x * (6 + -3x)) = 0 ((18 + -9x) + 2x * (6 + -3x)) = 0 (18 + -9x + (6 * 2x + -3x * 2x)) = 0 (18 + -9x + (12x + -6x2)) = 0 Combine like terms: -9x + 12x = 3x (18 + 3x + -6x2) = 0 Solving 18 + 3x + -6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(6 + x + -2x2) = 0 Factor a trinomial. 3((2 + -1x)(3 + 2x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Subproblem 2
Set the factor '(3 + 2x)' equal to zero and attempt to solve: Simplifying 3 + 2x = 0 Solving 3 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 0 + -3 2x = 0 + -3 Combine like terms: 0 + -3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5Solution
x = {2, -1.5}
| (-8x+8)2=4 | | (50-2x)*(25x+400)=204000 | | 34x+23.4=4(8.5x+4.1)+7 | | 7x+4y=4 | | -10x+17=-2(5x-5)+7 | | lnx+2+lnx+2=6 | | 2x-7=-14 | | log[5]5=x | | x*log[5](x)=18 | | (25k^2)=30 | | F(x+3)=x^2+kx-21 | | x^3+4x^2-19+14=0 | | x*(x-7)=228 | | =sin(9x) | | y=sin(9*x) | | 4[5x+5]=180 | | 3[5x+5]=75 | | 55=5[3x-4] | | -8x^2+16+x^4=0 | | 5[4x-3]=145 | | 236=4[7x+3] | | 7[3x-2]=70 | | 7[3x+3]=126 | | 180=6[4x+2] | | 6[7x-8]=246 | | 5[5x-3]=185 | | 5[3x+7]=125 | | 96=3[7x+4] | | 4[3x+2]=68 | | 3[7x-3]=159 | | 140=5[4x-4] | | -14+5x=3x+4 |